EFFECTS OF DEPTH AND CONCENTRATION OF DIGESTATE ON GROWTH OF THREE MICROALGAL SPECIES - Khanh, Nguyen Tran Thien (Vietnam Journal of Science and Technology, 2016)
In order to design a culture system for microalgal biomass production with a low cost and convenient cell collection, growth performance of mixtures of microalgal cells, including Euglena gracilis, Chlorella vulgaris, and Dunaliella tertiolecta cultured in a volume of 1 L were investigated at a PPFD of 300 µmol m-2 s-1 at the surface of the solution with continuous illumination at 30 °C. Each culture container contained diluted digestate at concentrations of 5, 10, 15, 20, and 50 %. Sample cells for counting cell number were collected daily at three depths: 0–50 mm (the surface layer), 10–15 mm (the middle layer), and 25–30 mm (the bottom layer). Pseudo-specific growth rates (ms) of each species at each depth were calculated as cellular multiplication rates using number of cells per time. In each layer, the average ms of each species was highest in 5 % digestate. The average ms of all three microalgal species (0.035 h-1) was observed in all layers in 5 % digestate solution. The ms of each species was highest in the bottom layer in 5% digestate (0.048 h-1, 0.041 h-1, and 0.022 h-1, respectively for C. vulgaris, E. gracilis, and D. tertiolecta). In conclusion, E. gracilis, C. vulgaris, and D. tertiolecta showed the highest specific growth rate in 5 % digestate in all layer.